Feasibility of using magnetic nanoparticles in water disinfection. (15th June 2021) - Santos, A. Sofia G.G.; Ramalho, Patrícia S.F.; Viana, A.T.; Lopes, A.R.; Gonçalves, Alexandra G.; Nunes, Olga C.; Pereira, M. Fernando R.; Soares, O. Salomé G.P.
Abstract: Disinfection is a crucial step during the water treatment process due to the significant risks of water contamination with human and animal excreta. The development of innovative disinfection technologies that can be applied at water point of use, avoiding contamination problems in water distribution systems and reservoirs, are needed. Thus, the present work aimed at assessing the disinfection efficiency of iron oxide magnetic nanoparticles (MNPs) modified with different compounds, such as carbon nanotubes, copper and silver, in water solutions contaminated with bacteria. Kinetic and influence of nanoparticles concentration experiments, performed with Escherichia coli, allowed to define the optimal reaction conditions to apply in batch experiments (1 min of contact time and 50 mg/mL of MNPs). During these experiments, CuFeO/CNT, C–FeO@CVD750 and 5% Ag/FeO were selected as the most efficient presenting log reduction values of 2.99, 1.50 and 2.11, respectively; however, experiments performed with Staphylococcus aureus suspension and a mixed bacterial suspension ( E. coli + S. aureus ) allowed to observe a slight decrease in nanomaterials efficiency, which was more evident for C–FeO@CVD750 and 5% Ag/FeO materials achieving efficiencies of 94 and 83% (corresponding log reductions of 1.26 and 0.77, respectively). CuFeO/CNT nanoparticles proved to be the most efficient material for both bacteria removal presenting an efficiency of 99% (corresponding log reduction of 1.99) for the mixed bacterial suspension. These nanoparticles proved to have great stability over successive experiments, and the low leaching values of the metals present in their composition after reaction proved the resistance and efficiency of these magnetic nanoparticles. Highlights: Several MNPs were synthesized to be applied in bacterial removal. MNPs proved to be efficient for the removal of different types of bacteria. CuFeO/CNT, C–FeO@CVD750 and 5% Ag/FeO presented good performances. MNPs were stable and showed small loss of efficiency after successive cycles. Promising results allow MNPs application for real water treatment.